2019
DOI: 10.3748/wjg.v25.i20.2514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blumgart anastomosis in reducing the incidence rate of pancreatic fistula after pancreatoduodenectomy

Abstract: BACKGROUND Pancreatic fistula is one of the most serious complications after pancreatoduodenectomy for treating any lesions at the pancreatic head. For years, surgeons have tried various methods to reduce its incidence. AIM To investigate and emphasize the clinical outcomes of Blumgart anastomosis compared with traditional anastomosis in reducing postoperative pancreatic fistula. METHODS In this observational study, a retrospective analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Of these, 18 were excluded because they were trial protocols [50][51][52][53] , review 39 , letter 54 , studies with no comparison with BA 18,[20][21][22][23][25][26][27][28][29] and studies related with BA versus pancreaticogastrostomy 55,56 . Ultimately, one RCT 30 (from Asia) and ten non-randomized comparative studies (2 from Europe 19,38 and 8 from Asia 24,[31][32][33][34][35][36][37] ) involving a total of 2412 patients were included in the quantitative syntheses. The process by which comparative studies were selected for inclusion in the present meta-analysis is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 18 were excluded because they were trial protocols [50][51][52][53] , review 39 , letter 54 , studies with no comparison with BA 18,[20][21][22][23][25][26][27][28][29] and studies related with BA versus pancreaticogastrostomy 55,56 . Ultimately, one RCT 30 (from Asia) and ten non-randomized comparative studies (2 from Europe 19,38 and 8 from Asia 24,[31][32][33][34][35][36][37] ) involving a total of 2412 patients were included in the quantitative syntheses. The process by which comparative studies were selected for inclusion in the present meta-analysis is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sample sizes ranged from 87 to 374 patients in individual studies. Four studies focused on the rate of POPF in soft pancreatic texture 30,[32][33][34] and eight reported the use of pancreatic duct stents, either internal or external 24,[30][31][32][33][34][35][36] . Octreotide was used in five studies selectively 19,24,30,37,38 .…”
Section: Trial Characteristics and Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some non-randomized, retrospective studies have recently reported the safety and feasibility of Blumgart anastomosis, a pancreaticojejunostomy method, showing its low postoperative mortality rate (1-3%), reoperation rate (5-7%), and acceptable POPF rate (15-20%). Furthermore, these studies have shown that Blumgart anastomosis is more effective with respect to other pancreatic anastomoses, minimizing severe complications [23][24][25][26]. However, all these studies were retrospective, their impact on the clinical evidence was poor, and they require confirmation by a randomized controlled trial.…”
Section: Discussionmentioning
confidence: 99%